2020
DOI: 10.1002/adfm.202004880
|View full text |Cite
|
Sign up to set email alerts
|

Charge Density Depinning in Defective MoTe2 Transistor by Oxygen Intercalation

Abstract: Molybdenum ditelluride is prone to various defects. Among them, tellurium vacancies lead to the significant reduction of band gap as revealed by density functional theory (DFT) calculations. They are responsible for inducing spatial band structure variation and localized charge puddles in MoTe 2. As a result, undesirable charge density pinning is anticipated in the channel-dominated MoTe 2 field-effect transistors (FETs) even with much improved ohmic contacts, resulting in poor device characteristics, for exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Our MoTe 2 samples are exhibiting more p-type behavior at high temperature, therefore, there is more probability of oxidation defects instead of Te vacancies because the chalcogenide vacancies in semiconducting TMDCs are typically reported to induce defect states close to the conduction band edge. [34] Liu et al reported charge traps depth of around 0.24 to 0.018 eV depending on applied V G , [21] and interestingly our measured E a range agrees with their provided numbers. With the increase of temperature, more charge carriers gain sufficient energy to surmount the defect states energy barrier.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our MoTe 2 samples are exhibiting more p-type behavior at high temperature, therefore, there is more probability of oxidation defects instead of Te vacancies because the chalcogenide vacancies in semiconducting TMDCs are typically reported to induce defect states close to the conduction band edge. [34] Liu et al reported charge traps depth of around 0.24 to 0.018 eV depending on applied V G , [21] and interestingly our measured E a range agrees with their provided numbers. With the increase of temperature, more charge carriers gain sufficient energy to surmount the defect states energy barrier.…”
Section: Resultssupporting
confidence: 90%
“…where k B is the Boltzmann constant. [20][21][22] Figure 6c shows the E a as a function of V G by fitting the Arrhenius plot between logarithmic of G and T −1 . The obtained E a values vary from 0.22 to 0.12 eV when V G was swept from 0 to 100 V, which approximately depicts the energy depth of charge traps around the valence band maxima.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 41 ] Oxygen has been intercalated into MoTe 2 to remove charge density pinning, which improves hole mobility up to 77 cm 2 V –1 s –1 and hole current density over 20 µA µm –1 . [ 42 ] Li intercalation in multilayer WSe 2 field‐effect transistor (FET) reduces both Schottky and electrostatic potential barriers at the vdW interfaces, thereby improving the carrier transport. [ 43 ] These superior performances resulted from intercalation may provide an excellent platform for high performance electronic and optoelectronic devices based on 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D materials, including graphene, transition metal dichalcogenides, and black phosphorous, have been attracting increasing interests during the past decade owing to their attractive properties, such as high carrier mobility, [1][2][3] tunable bandgap, [4] and anisotropic conductivity, [5] leading to possible applications in the fields of electronics [6,7] and optoelectronics. [8] To achieve specific functionalities, such as tuning the electronic properties, [9] contact engineering, [10] forming p-n junctions, doping techniques for 2D materials are necessary. For 2D materials, surface charge transfer has been demonstrated as an efficient doping technique.…”
Section: Introductionmentioning
confidence: 99%